Facilitation and sustainable agriculture: a mechanistic approach to reconciling crop production and conservation. (30th June 2015) - Brooker, Rob W.; Karley, Alison J.; Newton, Adrian C.; Pakeman, Robin J.; Schöb, Christian
Summary: Food security is currently considered a major global problem. However, increasing intensity of food production in agricultural systems has driven reductions in farmland biodiversity. A major challenge is to enable biodiversity conservation whilst addressing the problem of food security. Here we describe how facilitative plant–plant interactions in crop systems could be used to help strike this balance. An obvious example is that of intercropping systems, where combinations of crop species can – under some circumstances – deliver reduced inputs of agrochemicals (fertilizers, pesticides) per unit yield, with potential knock‐on benefits for biodiversity conservation. Other facilitative processes can also play a role in biodiversity conservation. Increased intraspecific crop genetic diversity can help protect crops from pests and diseases. Although overlooked in facilitation research, we argue that the mechanisms operate in a manner which is directly analogous to associational defence against herbivores, a process well recognized in the facilitation literature. As with intercropping, the benefits to nature conservation arise from reduced pesticide use per unit harvested crop. Crops may have facilitative effects on some arable weed species, particularly those that are currently considered rare in intensive farming systems. Work is in its early stages to understand the underlying mechanisms, but it appears that crops might create niche space to which some weed species are adapted. Increasing plant species diversity through niche space creation may then have cascading benefits for other components of farmland biodiversity. Our new understanding of facilitative processes arising from work on crop systems has lessons for the study of facilitative interactions in natural and semi‐natural communities. We argue that, although easier to identify and quantify in crop systems, some of these facilitative processes have to date been overlooked in studies of non‐crop systems and certainly deserve further consideration. Finally, we discuss what steps may be needed to move from our understanding of the role of facilitation to the development of new agricultural practice. In some cases the challenge may be one of the encouraging uptake of existing practices, and in others more research is needed to understand how new ecological understanding might deliver more sustainable agricultural practice. Abstract : Lay Summary